2022
DOI: 10.3390/jcm11123290
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Septum with or without Hysteroscopic Metroplasty: Impact on Fertility and Obstetrical Outcomes—A Systematic Review and Meta-Analysis of Observational Research

Abstract: Objective: we performed a systematic review/meta-analysis to evaluate the impact of septate uterus and hysteroscopic metroplasty on pregnancy rate-(PR), live birth rate-(LBR), spontaneous abortion-(SA) and preterm labor (PL) in infertile/recurrent miscarriage-(RM) patients. Data sources: a literature search of relevant papers was conducted using electronic bibliographic databases (Medline, Scopus, Embase, Science direct). Study eligibility criteria: we included in this meta-analysis all types of observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 81 publications
(333 reference statements)
2
13
0
Order By: Relevance
“…The reduction in miscarriage rate and preterm birth rate in our study was consistent with those found in a systematic review and meta-analysis [ 21 ]. Our findings regarding hysteroscopic septoplasty were also consistent with those found in a Systematic Review and Meta-Analysis of Observational Research [ 22 ]; a detrimental effect of the uterine septum was found on pregnancy rate, low birth rate, spontaneous abortion and preterm labor. Its treatment reduced the rate of spontaneous abortion [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in miscarriage rate and preterm birth rate in our study was consistent with those found in a systematic review and meta-analysis [ 21 ]. Our findings regarding hysteroscopic septoplasty were also consistent with those found in a Systematic Review and Meta-Analysis of Observational Research [ 22 ]; a detrimental effect of the uterine septum was found on pregnancy rate, low birth rate, spontaneous abortion and preterm labor. Its treatment reduced the rate of spontaneous abortion [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another meta-analysis by Noventa et al produced similar results with regard to recurrent miscarriage (OR 0.02, 95%CI 0.02-0.04), preterm labor (OR 0.05, 95%CI 0.03-0.08), with pregnancy rate still demonstrating no statistically significant difference [ 15 ]. An additional finding of this study was the statistically significant improvement in live birth rate (OR 3.07, 95%CI 1.22-7.73) in the hysteroscopic metroplasty group.…”
Section: Discussionmentioning
confidence: 88%
“…The current recommendation is to wait two months before conceiving postoperatively, and trial of labor is acceptable. A recent meta-analysis showed that metroplasty remains useful in infertile patients or in patients with a history of repeated spontaneous abortion, as treatment reduces the rate of spontaneous abortion, and increases live birth rate [26,27 ▪ ,28].…”
Section: The Role Of Surgical Interventionmentioning
confidence: 99%